A joint Chandra and Swift view of the 2015 X-Ray dust-scattering echo of V404 Cygni - Heinz, S.; Corrales, L.; Smith, R.; Brandt, W.; Jonker, P.; Plotkin, Richard; Neilsen, J. (Institute of Physics Publishing, 2016)
We present a combined analysis of the Chandra and Swift observations of the 2015 X-ray echo of V404 Cygni. Using a stacking analysis, we identify eight separate rings in the echo. We reconstruct the soft X-ray light curve of the 2015 June outburst using the high-resolution Chandra images and cross-correlations of the radial intensity profiles, indicating that about 70% of the outburst fluence occurred during the bright flare at the end of the outburst on MJD 57199.8. By deconvolving the intensity profiles with the reconstructed outburst light curve, we show that the rings correspond to eight separate dust concentrations with precise distance determinations. We further show that the column density of the clouds varies significantly across the field of view, with the centroid of most of the clouds shifted toward the Galactic plane, relative to the position of V404 Cyg, invalidating the assumption of uniform cloud column typically made in attempts to constrain dust properties from light echoes. We present a new XSPEC spectral dust-scattering model that calculates the differential dust-scattering cross section for a range of commonly used dust distributions and compositions and use it to jointly fit the entire set of Swift echo data. We find that a standard Mathis-Rumpl-Nordsieck model provides an adequate fit to the ensemble of echo data. The fit is improved by allowing steeper dust distributions, and models with simple silicate and graphite grains are preferred over models with more complex composition. © 2016. The American Astronomical Society. All rights reserved.